Method for preparing porous carbon rich in closed pores for hard carbon negative electrode material and application
Patent Information
- Application Number
- CN202410340011.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-03-25
AI Technical Summary
但是实际制备过程中往往形成的闭孔隙有限,难以进一步提升闭孔隙率,导致平台区的容量贡献难以提升
[0026] 1. This invention uses biomass-based porous carbon with high microporosity as a precursor. The method is simple and easy to implement, and can be used for large-scale preparation of hard carbon anode materials rich in closed pores.
Smart Images

Figure CN118239487B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy materials technology, specifically to a method and application for preparing hard carbon anode materials rich in closed pores from porous carbon. Background Technology
[0002] Global demand for electrochemical energy technologies is growing rapidly, particularly for advanced energy storage such as batteries. Lithium-ion batteries dominate among various battery energy storage technologies due to their high energy density, high power density, and long cycle life. However, the limited and uneven distribution of lithium resources, coupled with rising demand, has led to a significant increase in the cost of lithium-ion batteries, severely hindering their further development. Therefore, exploring more abundant and cost-effective electrochemical energy storage devices to reduce dependence on lithium is crucial for sustainable development. Sodium-ion batteries have attracted considerable attention in the field of large-scale energy storage due to their low cost, abundant sodium resources, and similar physicochemical properties to lithium. The commercial application of sodium-ion batteries largely depends on the development of high-performance, low-cost electrode materials. The anode material is a major bottleneck because commercial graphite cannot be used to store sodium ions. Among numerous carbon-based electrode materials, hard carbon materials, in particular, are considered the most suitable anode candidate for sodium-ion batteries due to their large interlayer spacing and abundant closed-cell structure, which ensures greater sodium ion storage.
[0003] To date, the vast majority of reports indicate that sodium ion storage behavior in hard carbon exhibits two characteristic regions: a ramp region between 2.5 and 0.1 V and a plateau region below 0.1 V. Sodium ion storage in the ramp region is attributed to defects, heteroatoms, open pores, and d-phase. 002 The adsorption behavior at intervals (>0.4 nm) in the plateau region is attributed to the intercalation of sodium ions in the graphite-like layers of hard carbon, and the filling of closed pores constructed by the twisted graphite-like layers. It is noteworthy that high-specific-capacity hard carbon cells dominated by the slope region typically exhibit excellent rate performance and cycle stability, but their high voltage reduces their value in practical applications. Therefore, improving the sodium ion storage capacity in the plateau region is crucial for enhancing practical full cells.
[0004] The storage capacity of sodium ions in the plateau region is closely related to nanopores, especially closed pores. Researchers have effectively improved the plateau region capacity by using various pore-forming strategies, such as pre-oxidation, introducing pore-forming agents (e.g., nano-sized MgO particles, ethanol, and organic polymers), and sealing the pore entrances of porous carbon. The porous structure of the precursor is a necessary condition for hard carbon materials to possess abundant closed pores. The formation of closed pores mainly originates from the transformation of open pores in the precursor. Micropores and mesopores are more likely to form closed pore structures during high-temperature carbonization, while macropores gradually shrink to form micropores and are less likely to form closed pore structures. The literature "Altering Thermal Transformation Pathway to Create Closed Pores in Coal-Derived Hard Carbon and Boosting of Na" + The authors of the paper "Plateau Storage for High-Performance Sodium-Ion Battery and Sodium-Ion Capacitor (Adv. Funct. Mater. 2022, 32, 2203725)" used KOH chemical activation to generate closed pores in the anthracite carbon framework, followed by etching of carbon microcrystals to create a disordered carbon structure. High temperature was then used to alter the thermal conversion pathway, enabling the recombination of the pre-formed open pores and disordered carbon structure, resulting in numerous closed nanopores within the carbon framework. However, intense etching reduced the graphitization degree of the graphite domain microcrystal structure, leading to decreased conductivity. Coal-based and pitch-based precursors, due to their soft carbon structure, face significant challenges in forming closed pores, resulting in low porosity. Biomass-based precursors, however, possess a natural nanoporous structure, and the resulting graphite domain microcrystals exhibit highly cross-linked structures. However, in actual fabrication processes, the number of closed pores formed is often limited, making it difficult to further increase the closed porosity and thus hindering the capacity contribution of the plateau region.
[0005] Therefore, how to adopt a suitable strategy to prepare hard carbon anode materials rich in closed pores is one of the focal points in the field of hard carbon anode materials. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a hard carbon anode material rich in closed pores using porous carbon. This invention uses biomass cotton stalks as raw material, potassium carbonate (K2CO3) and potassium hydroxide (KOH) as activators. The weak etching ability of K2CO3 inhibits the strong activation reaction of KOH, resulting in a biomass-based porous carbon precursor with high microporosity. Then, combined with high-temperature crystal transformation and chemical vapor deposition processes, a hard carbon anode material rich in closed pores is prepared, which significantly improves the capacity contribution of the plateau region and achieves excellent sodium storage performance.
[0007] To achieve the above-mentioned objectives, the technical solution of the present invention is as follows:
[0008] This invention provides a method for preparing hard carbon anode materials rich in closed pores from porous carbon, comprising the following steps:
[0009] (1) Weigh a certain amount of cotton stalks and dry and crush them;
[0010] (2) Take the crushed cotton stalks and place them in a tube furnace under an argon or nitrogen atmosphere for pre-carbonization;
[0011] (3) Mix the pre-carbonized carbonized material with the activator (K2CO3 and KOH) uniformly according to the mass percentage;
[0012] (4) The material obtained in step (3) is heated to 600-800℃ in a tube furnace under the protection of argon or nitrogen atmosphere to carry out the activation reaction. The weak etching ability of K2CO3 will inhibit the strong activation reaction of KOH, so that the activation reaction process tends to be mild. After cooling to room temperature, the biomass-based porous carbon mixed material is obtained.
[0013] (5) The porous carbon mixture obtained in step (4) is washed in hydrochloric acid solution and deionized water until the solution is neutral to obtain a biomass-based porous carbon precursor with high microporosity.
[0014] (6) The porous carbon material obtained in step (5) is placed in a high-temperature furnace under an argon or nitrogen atmosphere to carry out a high-temperature reaction in order to regulate the graphite domain microcrystalline structure of the carbon skeleton in the porous carbon. At the same time, some open pores close to form closed pores, thus obtaining a porous hard carbon anode material.
[0015] (7) The hard carbon anode material obtained in step (6) is placed in a tube furnace and chemical vapor deposition reaction is carried out under the atmosphere of argon or nitrogen and carbon-containing mixed gas. Carbon is fully deposited in the open pores on the surface of the porous hard carbon material, thereby obtaining a hard carbon anode material rich in closed pores.
[0016] Preferably, the particle size of the cotton stalk powder in step (1) is 5-20 μm, more preferably 5-10 μm. Preferably, the pre-carbonization temperature in step (2) is 300-700℃ (preferably 600℃) to ensure that the cellulose carbon source of the biomass cotton stalk is fully carbonized.
[0017] Preferably, in step (2), the pre-carbonization heating rate is 5-10℃ / min, and the pre-carbonization time is 3-5h. Preferably, in step (3), the mass percentage of the carbonized material and the activator after pre-carbonization is 100%-400% to ensure sufficient activation of the carbonized material, wherein KOH and K2CO3 are in an optimal mass ratio of 1:1.
[0018] Preferably, the activation reaction temperature in step (4) is 600-800℃ (preferably 700℃), the reaction time is 2-5h, and the heating rate is 5℃ / min. The activation reaction is carried out under mild conditions, depending on the intensity of the activation reaction between KOH and K2CO3 and the carbonized material.
[0019] Preferably, in step (5), the concentration of the hydrochloric acid solution is 0.5-2 mol / L, and the stirring time is 5-10 h. Preferably, in step (6), the high-temperature reaction temperature is 1100-1500℃, the reaction time is 3-5 h, and the heating rate is 5-10℃ / min, so as to regulate the graphite domain microcrystalline structure of the carbon skeleton in porous carbon, while ensuring that the open pores can close to form closed pores.
[0020] Preferably, the carbon source in step (7) includes benzene, toluene, pyridine, and furan, wherein one or more of these can be used in any combination.
[0021] Preferably, in step (7), the gas flow rate of argon or nitrogen is 100-200 mL / min, and the volume concentration of carbon source gas is not less than 10% to ensure that the surface openings are fully deposited.
[0022] Preferably, the chemical vapor deposition reaction temperature in step (7) is 600-900℃ (preferably 700℃), the heating rate is 10℃ / min, and the deposition time is 1-3h. By controlling the reaction temperature, the graphitization degree of the deposited carbon can be adjusted, and by controlling the deposition time, the deposition amount can be adjusted, ensuring that all open pores are closed and transformed into closed pores.
[0023] The present invention also provides a hard carbon anode material for sodium-ion batteries, characterized in that it is a hard carbon anode material rich in closed pores prepared by any combination of the above-mentioned technical solutions through activation-high temperature-chemical vapor deposition.
[0024] This invention uses the above-mentioned hard carbon anode material rich in closed pores to prepare electrode sheets and assemble them into sodium-ion batteries.
[0025] The technical effects achieved by this invention are as follows:
[0026] 1. This invention uses biomass-based porous carbon with high microporosity as a precursor. The method is simple and easy to implement, and can be used for large-scale preparation of hard carbon anode materials rich in closed pores.
[0027] 2. The closed-pore-rich hard carbon anode material prepared in this invention first activates the pre-carbonized material using potassium carbonate (K2CO3) and potassium hydroxide (KOH) as activators. The weak etching ability of K2CO3 suppresses the strong activation reaction of KOH, resulting in a biomass-based porous carbon precursor with high microporosity. High-temperature crystal transformation and chemical vapor deposition are then used to convert the open pores into a closed-pore structure.
[0028] 3. The hard carbon anode material rich in closed pores of the present invention has the following advantages: the hard carbon microstructure has abundant closed pores, which provides an ultra-high capacity contribution to the capacity improvement of the plateau region; the highly cross-linked graphite domain structure of the biomass-based porous carbon skeleton has multi-channel sodium intercalation pathways, which provides rapid kinetic characteristics. The above advantages synergistically improve the sodium storage performance of the hard carbon anode material. Attached Figure Description
[0029] Figure 1 The XRD diffraction pattern of the hard carbon anode material rich in closed pores prepared in Example 1 of the present invention;
[0030] Figure 2 The nitrogen adsorption-desorption curve of the hard carbon anode material rich in closed pores prepared in Example 1 of the present invention is shown.
[0031] Figure 3 The pore size distribution diagram is shown for the hard carbon anode material rich in closed pores prepared in Example 1 of the present invention.
[0032] Figure 4 TEM image of the hard carbon anode material rich in closed pores prepared in Example 1 of the present invention;
[0033] Figure 5 The first charge-discharge curve of the hard carbon anode material rich in closed pores prepared in Example 1 of the present invention;
[0034] Figure 6 The rate performance of the hard carbon anode material rich in closed pores prepared in Example 1 of this invention.
[0035] Figure 7 The cycling performance of the hard carbon anode material rich in closed pores prepared in Example 1 of this invention is shown. Detailed Implementation
[0036] This invention uses biomass cotton stalks as raw material, potassium carbonate (K2CO3) and potassium hydroxide (KOH) as activators. The weak etching ability of K2CO3 inhibits the strong activation reaction of KOH, resulting in a biomass-based porous carbon precursor with high microporosity. Then, combined with high-temperature crystal transformation and chemical vapor deposition processes, a hard carbon anode material rich in closed pores is prepared.
[0037] The hard carbon anode material prepared by this invention has abundant closed-pore structures in its microstructure, which provides a good capacity contribution for the pore filling and storage of sodium ions in the plateau region; the highly cross-linked graphite domain structure of the biomass-based porous carbon skeleton has multi-channel sodium intercalation pathways and rapid kinetic characteristics, thereby improving the sodium storage performance of the hard carbon anode material.
[0038] This invention provides a method for preparing hard carbon anode materials rich in closed pores from porous carbon, comprising the following steps:
[0039] (1) Weigh a certain amount of cotton stalks and dry and crush them;
[0040] (2) Take the crushed cotton stalks and place them in a tube furnace under an argon or nitrogen atmosphere for pre-carbonization;
[0041] (3) Mix the pre-carbonized carbonized material with the activator (K2CO3 and KOH) in a uniform mass percentage; (4) Heat the uniformly mixed material obtained in step (3) to 600-800℃ in a tube furnace under the protection of argon or nitrogen atmosphere for activation reaction. The weak etching ability of K2CO3 will inhibit the strong activation reaction of KOH, making its activation reaction process more moderate. After cooling to room temperature, the biomass-based porous carbon mixture material is obtained.
[0042] (5) The porous carbon mixture obtained in step (4) is washed in hydrochloric acid solution and deionized water until the solution is neutral to obtain a biomass-based porous carbon precursor with high microporosity.
[0043] (6) The porous carbon material obtained in step (5) is placed in a high-temperature furnace under an argon or nitrogen atmosphere to carry out a high-temperature reaction in order to regulate the graphite domain microcrystalline structure of the carbon skeleton in the porous carbon. At the same time, some open pores close to form closed pores, thus obtaining a porous hard carbon anode material.
[0044] (7) The hard carbon anode material obtained in step (6) is placed in a tube furnace and chemical vapor deposition reaction is carried out under the atmosphere of argon or nitrogen and carbon-containing mixed gas. Carbon is fully deposited in the open pores on the surface of the porous hard carbon material, thereby obtaining a hard carbon anode material rich in closed pores.
[0045] Example 1
[0046] (1) Weigh 500g of dried and pulverized cotton stalks with a particle size of less than 10μm. Pre-carbonize the stalks in a tube furnace under an argon or nitrogen atmosphere. The pre-carbonization temperature is 600℃, the pre-carbonization time is 3h, and the heating rate is 10℃ / min. After cooling to room temperature, the pre-carbonized material is obtained. The heating rate of 10℃ / min ensures rapid carbonization of cellulose molecules, and carbonization at 600℃ for 3h ensures that cellulose is fully carbonized and converted into a carbon structure. Excessive temperature, excessive time, and excessively slow heating rate will affect the formation and microstructure of the carbonized material.
[0047] (2) Weigh 10g of carbide and mix it evenly with activators (KOH and K2CO3) according to the mass percentage. The total mass percentage of KOH and K2CO3 is 200%, with 10g of KOH and 10g of K2CO3. Experiments have verified that the most suitable mass ratio of KOH to K2CO3 is 1:1. The optimal mass ratio ensures that K2CO3 has the best effect in suppressing the strong etching effect of KOH. When the total mass percentage of activators is 200%, the microporosity of the carbide and the microcrystalline structure of the carbon skeleton can achieve the optimal combination. If the total mass percentage of activators is too high or too low, it will affect the control of the pore structure of the carbide and the graphitization degree of the carbon skeleton.
[0048] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere. The reaction temperature is 700℃, the reaction time is 5h, the heating rate is 5℃ / min, and after cooling to room temperature, the biomass-based porous carbon mixed material is taken out and washed.
[0049] (4) The porous carbon mixture obtained in step (3) is washed with 1 mol / L hydrochloric acid solution and stirred for 5 h. The solution is washed with deionized water until neutral and then dried in a forced-air drying oven for 12 h to obtain a biomass-based porous carbon precursor with high microporosity.
[0050] (5) The porous carbon material obtained in step (4) is placed in a high-temperature furnace under an argon or nitrogen atmosphere for a high-temperature reaction at 1300℃ for 4 hours at a heating rate of 5℃ / min. After cooling to room temperature, a porous hard carbon anode material is obtained where some open pores close to form closed pores. Experiments have verified that holding at 1300℃ for 4 hours is the optimal condition for controlling the closure of open pores to form closed pores and the graphite domain microcrystalline structure of the carbon skeleton in porous carbon.
[0051] (6) The porous hard carbon material obtained in step (5) is placed in a tube furnace and plugged by chemical vapor deposition under an atmosphere of argon or a mixture of nitrogen and benzene. The deposition temperature is 700℃, the reaction time is 2h, and the heating rate is 10℃ / min. Experiments have verified that the 700℃ deposition for 2h is mainly to ensure that all open pores on the surface are fully deposited, and the heating rate of 10℃ / min is the optimal heating rate. Too high a deposition temperature, too long a time, and too slow a heating rate will affect the deposition effect. After cooling to room temperature, a hard carbon anode material rich in closed pores is obtained.
[0052] (7) Fabrication of electrode sheets. The prepared hard carbon negative electrode material rich in closed pores, conductive carbon black, and binder PVDF are weighed in a mass ratio of 80:10:10 and placed in a mortar and mixed evenly. An appropriate amount of N-methylpyrrolidone (NMP) solvent is added and stirred evenly to obtain a slurry. The slurry is then evenly coated on aluminum (Al) foil and dried in a vacuum drying oven at 120°C for 12 hours. The slurry is then cut into 12 mm circular negative electrode sheets for later use.
[0053] (8) The coin cell assembly was carried out in a double-station glove box filled with argon atmosphere. The prepared hard carbon material electrode sheet was used as the negative electrode sheet, the commercial electrolyte 1M NaPF6 DIGLYME=100Vol% was used as the electrolyte, and the metal Na sheet was used as the counter electrode to assemble the coin cell.
[0054] (9) The assembled 2032 button cell was charged and discharged on a constant current testing system with a voltage range of 0.001-2.4V.
[0055] Figure 1 The figures show the XRD patterns of the high microporosity biomass-based porous carbon precursor and the hard carbon anode material rich in closed pores prepared in Example 1 of this invention. As can be seen from the figures, the (002) peak of the high microporosity biomass-based porous carbon precursor almost disappears, indicating low crystallinity. This suggests that the micropores formed after activation lead to more disordered carbon atoms. The XRD pattern of the hard carbon rich in closed pores shows high crystallinity, especially with the (002) peak even approaching the position of graphite, indicating the formation of graphite-like domains in the hard carbon. The shift from highly disordered carbon atoms to the formation of graphite-like domains demonstrates that the increased degree of graphitization and the growth of graphite domains lead to the closure of open pores, forming closed pores.
[0056] Figure 2 The figures show the nitrogen adsorption-desorption curves of the high microporosity biomass-based porous carbon precursor and the hard carbon anode material rich in closed pores prepared in Example 1 of this invention. As can be seen from the figure, the biomass-based porous carbon precursor has a rich microporous structure. After being converted into the corresponding hard carbon, the specific surface area is significantly reduced, indicating that a large number of micropores are closed to form a closed-pore structure.
[0057] Figure 3 The diagram shows the pore size distribution of the high microporosity biomass-based porous carbon precursor and the hard carbon anode material rich in closed pores prepared in Example 1 of this invention. The biomass-based porous carbon precursor contains a large number of micropores of about 0.7 nm, while the corresponding hard carbon does not show any open pores.
[0058] Figure 4 This is a TEM image of the hard carbon anode material rich in closed pores prepared in Example 1 of the present invention; it can be clearly seen that there is a rich closed pore structure, which is beneficial to the sodium storage capacity contribution of the plateau region; the closed pores are mainly formed by turbine-shaped graphite domains, while the edges have long graphite-like graphite domains, which have high electrical conductivity.
[0059] Figure 5 The first charge-discharge curve of the hard carbon anode material rich in closed pores prepared in Example 1 of this invention; at 20 mAg -1 At current density, the charging specific capacity reaches as high as 443.3 mAh g. -1The high capacity, with the platform contributing up to 273.7 mAh g. -1 , accounting for 61.7%. The high platform capacity contribution is attributed to the abundance of closed-cell structures.
[0060] Figure 6 The figure shows the rate performance of the hard carbon anode material rich in closed pores prepared in Example 1 of this invention; as can be seen from the figure, in 2Ag -1 At the current density, the reversible specific capacity is 281.2 mAh g. -1 The superior rate performance is attributed to the high electrical conductivity and fast kinetic properties of the closed-pore turbine-shaped graphite domains and edge-like graphite domains.
[0061] Figure 7 The figure shows the cycling performance of the hard carbon anode material rich in closed pores prepared in Example 1 of this invention; as can be seen from the figure, at 500 mAg... -1 At current density, the capacity retention rate is 76.9% after 500 cycles and 70.4% after 1000 cycles. The excellent cycling stability is attributed to the high structural stability of the turbine-shaped graphite domains that form closed pores and the graphite domains of edge-like graphite.
[0062] Comparative Example 1
[0063] (1) Weigh 500g of dried and pulverized cotton stalks with a particle size of less than 10μm. Pre-carbonize the stalks in a tube furnace under an argon or nitrogen atmosphere. The pre-carbonization temperature is 600℃, the pre-carbonization time is 3h, and the heating rate is 10℃ / min. After cooling to room temperature, the pre-carbonized material is obtained. The heating rate of 10℃ / min ensures rapid carbonization of cellulose molecules, and carbonization at 600℃ for 3h ensures that cellulose is fully carbonized and converted into a carbon structure. Excessive temperature, excessive time, and excessively slow heating rate will affect the formation and microstructure of the carbonized material.
[0064] (2) Weigh 10g of carbonized material and place it in a high-temperature furnace under an argon or nitrogen atmosphere for a high-temperature reaction. The reaction temperature is 1300℃, the reaction time is 4h, the heating rate is 5℃ / min, and after cooling to room temperature, a porous hard carbon anode material is obtained.
[0065] (3) The porous hard carbon material obtained in step (2) is placed in a tube furnace and plugged by chemical vapor deposition under an atmosphere of argon or a mixture of nitrogen and benzene. The deposition temperature is 700℃, the reaction time is 2h, the heating rate is 10℃ / min, and the hard carbon anode material is obtained after cooling to room temperature.
[0066] Analysis of the above comparative example 1 shows that the pre-carbonized carbon material does not have the porous carbon characteristics of high microporosity, which means that the subsequent high-temperature reaction and chemical vapor deposition cannot form a rich closed-pore structure, resulting in a small contribution to the platform capacity.
[0067] Comparative Example 2
[0068] (1) Weigh 500g of dried and pulverized cotton stalks with a particle size of less than 10μm. Pre-carbonize the stalks in a tube furnace under an argon or nitrogen atmosphere. The pre-carbonization temperature is 600℃, the pre-carbonization time is 3h, and the heating rate is 10℃ / min. After cooling to room temperature, the pre-carbonized material is obtained. The heating rate of 10℃ / min ensures rapid carbonization of cellulose molecules, and carbonization at 600℃ for 3h ensures that cellulose is fully carbonized and converted into a carbon structure. Excessive temperature, excessive time, and excessively slow heating rate will affect the formation and microstructure of the carbonized material.
[0069] (2) Weigh 10g of carbide and mix it evenly with activators (KOH and K2CO3) according to the mass percentage. The total mass percentage of KOH and K2CO3 is 200%, with 10g of KOH and 10g of K2CO3. Experiments have verified that the most suitable mass ratio of KOH to K2CO3 is 1:1. The optimal mass ratio ensures that K2CO3 has the best effect in suppressing the strong etching effect of KOH. When the total mass percentage of activators is 200%, the microporosity of the carbide and the microcrystalline structure of the carbon skeleton can achieve the optimal combination. If the total mass percentage of activators is too high or too low, it will affect the control of the pore structure of the carbide and the graphitization degree of the carbon skeleton.
[0070] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere. The reaction temperature is 700℃, the reaction time is 5h, the heating rate is 5℃ / min, and after cooling to room temperature, the biomass-based porous carbon mixed material is taken out and washed.
[0071] (4) The porous carbon mixture obtained in step (3) is washed with 1 mol / L hydrochloric acid solution and stirred for 5 h. The solution is washed with deionized water until neutral and then dried in a forced-air drying oven for 12 h to obtain a biomass-based porous carbon precursor with high microporosity.
[0072] (5) The porous carbon material obtained in step (4) is placed in a high-temperature furnace under an argon or nitrogen atmosphere for a high-temperature reaction at 1300℃ for 4 hours at a heating rate of 5℃ / min. After cooling to room temperature, a porous hard carbon anode material is obtained where some open pores close to form closed pores. Experiments have verified that holding at 1300℃ for 4 hours is the optimal condition for controlling the closure of open pores to form closed pores and the graphite domain microcrystalline structure of the carbon skeleton in porous carbon.
[0073] Analysis of the above comparative example 2 shows that the high-temperature reaction can cause the open pores of the biomass-based porous carbon precursor with high microporosity to close and form closed pores. However, some open pores on the surface still remain and cannot be closed, resulting in limited capacity improvement in the plateau region and low initial coulombic efficiency.
[0074] Comparative Example 3
[0075] (1) Weigh 500g of dried and pulverized cotton stalks with a particle size of less than 10μm. Pre-carbonize the stalks in a tube furnace under an argon or nitrogen atmosphere. The pre-carbonization temperature is 600℃, the pre-carbonization time is 3h, and the heating rate is 10℃ / min. After cooling to room temperature, the pre-carbonized material is obtained. The heating rate of 10℃ / min ensures rapid carbonization of cellulose molecules, and carbonization at 600℃ for 3h ensures that cellulose is fully carbonized and converted into a carbon structure. Excessive temperature, excessive time, and excessively slow heating rate will affect the formation and microstructure of the carbonized material.
[0076] (2) Weigh 10g of carbonized material and activator (KOH) and mix them evenly according to the mass percentage. The total mass percentage of KOH is 200%, of which 20g of KOH is weighed.
[0077] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere. The reaction temperature is 700℃, the reaction time is 5h, the heating rate is 5℃ / min, and after cooling to room temperature, the biomass-based porous carbon mixed material is taken out and washed.
[0078] (4) The porous carbon mixture obtained in step (3) is washed with 1 mol / L hydrochloric acid solution and stirred for 5 h. The solution is washed with deionized water until neutral and then dried in a forced-air drying oven for 12 h to obtain biomass-based porous carbon precursor.
[0079] (5) The porous carbon material obtained in step (4) is placed in a high-temperature furnace under an argon or nitrogen atmosphere and subjected to a high-temperature reaction at a temperature of 1300℃ for 4 hours and a heating rate of 5℃ / min. After cooling to room temperature, a porous hard carbon anode material is obtained in which some open pores close to form closed pores.
[0080] (6) The porous hard carbon material obtained in step (5) is placed in a tube furnace and plugged by chemical vapor deposition under an atmosphere of argon or a mixture of nitrogen and benzene. The deposition temperature is 700℃, the reaction time is 2h, and the heating rate is 10℃ / min. After cooling to room temperature, the hard carbon anode material is obtained.
[0081] Analysis of the above comparative example 3 shows that due to the strong etching and activation effect of KOH, the proportion of micropores in the porous carbon precursor is low. At the same time, the mesopores formed cannot confine the growth of graphite domain microcrystals of carbon deposited by chemical vapor deposition, and the carbon skeleton graphite domains are cut off, resulting in low sodium storage capacity.
[0082] Example 2
[0083] (1) Weigh 500g of dried and pulverized cotton stalks with a particle size of less than 10μm. Pre-carbonize the stalks in a tube furnace under an argon or nitrogen atmosphere. The pre-carbonization temperature is 600℃, the pre-carbonization time is 3h, and the heating rate is 10℃ / min. After cooling to room temperature, the pre-carbonized material is obtained. The heating rate of 10℃ / min ensures rapid carbonization of cellulose molecules, and carbonization at 600℃ for 3h ensures that cellulose is fully carbonized and converted into a carbon structure. Excessive temperature, excessive time, and excessively slow heating rate will affect the formation and microstructure of the carbonized material.
[0084] (2) Weigh 10g of carbide and mix it evenly with activators (KOH and K2CO3) according to the mass percentage. The total mass percentage of KOH and K2CO3 is 300%, of which 15g of KOH and 15g of K2CO3 are used. Experiments have verified that the most suitable mass ratio of KOH to K2CO3 is 1:1. The optimal mass ratio ensures that K2CO3 has the best effect in inhibiting the strong etching of KOH. When the total mass percentage of activator is 200%, the microporosity of the carbide and the microcrystalline structure of the carbon skeleton can achieve the optimal combination. If the total mass percentage of activator is too high or too low, it will affect the control of the pore structure of the carbide and the graphitization degree of the carbon skeleton.
[0085] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere. The reaction temperature is 700℃, the reaction time is 5h, the heating rate is 5℃ / min, and after cooling to room temperature, the biomass-based porous carbon mixed material is taken out and washed.
[0086] (4) The porous carbon mixture obtained in step (3) is washed with 1 mol / L hydrochloric acid solution and stirred for 5 h. The solution is washed with deionized water until neutral and then dried in a forced-air drying oven for 12 h to obtain a biomass-based porous carbon precursor with high microporosity.
[0087] (5) The porous carbon material obtained in step (4) is placed in a high-temperature furnace under an argon or nitrogen atmosphere for a high-temperature reaction at 1300℃ for 4 hours at a heating rate of 5℃ / min. After cooling to room temperature, a porous hard carbon anode material is obtained where some open pores close to form closed pores. Experiments have verified that holding at 1300℃ for 4 hours is the optimal condition for controlling the closure of open pores to form closed pores and the graphite domain microcrystalline structure of the carbon skeleton in porous carbon.
[0088] (6) The porous hard carbon material obtained in step (5) is placed in a tube furnace and plugged by chemical vapor deposition under an atmosphere of argon or a mixture of nitrogen and benzene. The deposition temperature is 700℃, the reaction time is 3h, and the heating rate is 10℃ / min. Experiments have verified that the 700℃ deposition for 3h is mainly to ensure that all open pores on the surface are fully deposited, and the heating rate of 10℃ / min is the optimal heating rate. Too high a deposition temperature, too long a time, and too slow a heating rate will affect the deposition effect. After cooling to room temperature, a hard carbon anode material rich in closed pores is obtained.
[0089] Analysis of the above embodiments shows that excessive activator leads to over-activation, which increases the pore size of the porous carbon precursor, hinders pore opening and closing, and prevents the platform capacity from being improved.
[0090] Example 3
[0091] (1) Weigh 500g of dried and pulverized cotton stalks with a particle size of less than 10μm. Pre-carbonize the stalks in a tube furnace under an argon or nitrogen atmosphere. The pre-carbonization temperature is 600℃, the pre-carbonization time is 3h, and the heating rate is 10℃ / min. After cooling to room temperature, the pre-carbonized material is obtained. The heating rate of 10℃ / min ensures rapid carbonization of cellulose molecules, and carbonization at 600℃ for 3h ensures that cellulose is fully carbonized and converted into a carbon structure. Excessive temperature, excessive time, and excessively slow heating rate will affect the formation and microstructure of the carbonized material.
[0092] (2) Weigh 10g of carbide and mix it evenly with activator (KOH and K2CO3) according to the mass percentage. The total mass percentage of KOH and K2CO3 is 400%, with 20g of KOH and 20g of K2CO3. Experiments have verified that the most suitable mass ratio of KOH to K2CO3 is 1:1. The optimal mass ratio ensures that K2CO3 has the best effect in inhibiting the strong etching of KOH. When the total mass percentage of activator is 200%, the microporosity of the carbide and the microcrystalline structure of the carbon skeleton can achieve the optimal combination. If the total mass percentage of activator is too high or too low, it will affect the control of the pore structure of the carbide and the graphitization degree of the carbon skeleton.
[0093] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere. The reaction temperature is 700℃, the reaction time is 5h, the heating rate is 5℃ / min, and after cooling to room temperature, the biomass-based porous carbon mixed material is taken out and washed.
[0094] (4) The porous carbon mixture obtained in step (3) is washed with 1 mol / L hydrochloric acid solution and stirred for 5 h. The solution is washed with deionized water until neutral and then dried in a forced-air drying oven for 12 h to obtain a biomass-based porous carbon precursor with high microporosity.
[0095] (5) The porous carbon material obtained in step (4) is placed in a high-temperature furnace under an argon or nitrogen atmosphere for a high-temperature reaction at 1300℃ for 4 hours at a heating rate of 5℃ / min. After cooling to room temperature, a porous hard carbon anode material is obtained where some open pores close to form closed pores. Experiments have verified that holding at 1300℃ for 4 hours is the optimal condition for controlling the closure of open pores to form closed pores and the graphite domain microcrystalline structure of the carbon skeleton in porous carbon.
[0096] (6) The porous hard carbon material obtained in step (5) is placed in a tube furnace and plugged by chemical vapor deposition under an atmosphere of argon or a mixture of nitrogen and benzene. The deposition temperature is 700℃, the reaction time is 3h, and the heating rate is 10℃ / min. Experiments have verified that the 700℃ deposition for 3h is mainly to ensure that all open pores on the surface are fully deposited, and the heating rate of 10℃ / min is the optimal heating rate. Too high a deposition temperature, too long a time, and too slow a heating rate will affect the deposition effect. After cooling to room temperature, a hard carbon anode material rich in closed pores is obtained.
[0097] Analysis of the above embodiments shows that due to excessive activator content and over-activation, a porous carbon precursor with high microporosity cannot be formed, the pores cannot be closed, and the graphite domain microcrystalline structure of the carbon skeleton is etched and destroyed, resulting in a poor graphite domain structure and thus the platform capacity cannot be improved.
[0098] This invention prepares a biomass-based porous carbon precursor with high microporosity using a suitable activator. Combined with high-temperature reaction to close the pores and chemical vapor deposition process, a hard carbon anode material rich in closed pores is obtained. The abundant closed-pore structure enhances the capacity contribution of the plateau region. The biomass-based porous carbon framework with highly cross-linked graphite domain structure has multiple sodium intercalation pathways, thereby synergistically improving the sodium storage performance of the hard carbon anode material.
[0099] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention. The scope of protection claimed by the appended claims and their equivalents is defined.
Claims
1. A method for preparing a hard carbon anode material rich in closed pores from porous carbon, characterized in that, Includes the following steps: (1) Weigh a certain amount of cotton stalks and dry and crush them; (2) Take the crushed cotton stalks and place them in a tube furnace under an argon or nitrogen atmosphere for pre-carbonization; (3) Mix the pre-carbonized carbonized material and the activator evenly according to the mass percentage; (4) The material obtained in step (3) is uniformly mixed and activated in a tube furnace under the protection of argon or nitrogen atmosphere. After cooling to room temperature, it is taken out to obtain biomass-based porous carbon mixed material. (5) The porous carbon mixture obtained in step (4) is washed in hydrochloric acid solution and deionized water until the solution is neutral to obtain a biomass-based porous carbon precursor with high microporosity. (6) The porous carbon material obtained in step (5) is placed in a high-temperature furnace under an argon or nitrogen atmosphere to carry out a high-temperature reaction in order to regulate the graphite domain microcrystalline structure of the carbon skeleton in the porous carbon. At the same time, some open pores close to form closed pores, thus obtaining a porous hard carbon anode material. (7) The hard carbon anode material obtained in step (6) is placed in a tube furnace and chemical vapor deposition reaction is carried out under the atmosphere of argon or nitrogen and carbon-containing mixed gas. Carbon is fully deposited in the open pores on the surface of the porous hard carbon material to prepare a hard carbon anode material rich in closed pores. In step (2), the pre-carbonization temperature of the cotton stalks placed in the tube furnace under an argon or nitrogen atmosphere is 350-750℃; the heating rate is 5-10℃ / min; and the pre-carbonization time is 3-5h. The mass of the activator in step (3) is 200%-400% of the mass of the carbonized material, wherein the activator is K2CO3 and KOH, and the mass ratio of KOH to K2CO3 is 1:1; The activation reaction temperature in step (4) is 600-800℃; the reaction time is 2-5h; and the heating rate is 5℃ / min. The porous carbon material obtained in step (6) is placed in a high-temperature furnace under an argon or nitrogen atmosphere for a high-temperature reaction. The reaction temperature is 1100-1500℃, the reaction time is 3-5h, and the heating rate is 5-10℃ / min. In step (7), the carbon source includes one or more of benzene, toluene, pyridine or furan; the carrier gas is argon or nitrogen, the gas flow rate is 100-200 mL / min, and the volume concentration of carbon-containing gas in the mixed atmosphere is not less than 10%; the chemical vapor deposition reaction temperature is 600-900℃, the heating rate is 10℃ / min, and the deposition time is 1-3h.
2. A hard carbon anode material rich in closed pores, wherein the material is obtained by the preparation method described in claim 1; characterized in that: Biomass-based porous carbon precursors have high microporosity, while hard carbon anode materials have abundant closed pores, and the graphite domain structure of the biomass-based porous carbon framework is highly cross-linked.
3. Sodium-ion batteries, characterized by: This includes sodium-ion battery anode materials, wherein the anode material is a hard carbon anode material rich in closed pores prepared by the preparation method described in claim 1.
Citation Information
Patent Citations
Negative electrode particle and preparation method thereof, negative electrode plate and energy storage device
CN116314729A
Hard carbon material and preparation method thereof, negative electrode material and alkali metal ion battery
CN116692830A
Preparation method of sodium ion battery negative electrode hard carbon material with closed microporous structure
CN117003237A
Activated carbon prepared through nitrogen-rich hydrolysate enhanced hydrothermal nitrogen doping and room-temperature desulfurization application of activated carbon
CN117163957A